Retention of Activity by Antibodies Immobilized on Gold Nanoparticles of Different Sizes: Fluorometric Method of Determination and Comparative Evaluation - Dmitriy V. Sotnikov (MDPI AG, 2021)
Antibody–nanoparticle conjugates are widely used analytical reagents. An informative parameter reflecting the conjugates’ properties is the number of antibodies per nanoparticle that retain their antigen-binding ability. Estimation of this parameter is characterized by a lack of simple, reproducible methods. The proposed method is based on the registration of fluorescence of tryptophan residues contained in proteins and combines sequential measurements of first the immobilized antibody number and then the bound protein antigen number. Requirements for the measurement procedure have been determined to ensure reliable and accurate results. Using the developed technique, preparations of spherical gold nanoparticles obtained by the most common method of citrate reduction of gold salts (the Turkevich–Frens method) and varying in average diameter from 15 to 55 nm have been characterized. It was shown that the number of antibodies (immunoglobulins G) bound by one nanoparticle ranged from 30 to 194 during adsorptive unoriented monolayer immobilization. C-reactive protein was considered as the model antigen. The percentage of antibody valences that retained their antigen-binding properties in the conjugate increased from 17 to 34% with an increase in the diameter of gold nanoparticles. The proposed method and the results of the study provide tools to assess the capabilities of the preparations of gold nanoparticles and their conjugates as well as the expediency of seeking the best techniques for various practical purposes.